A proposed guidance program for the Philippine College of Commerce laboratory high school - Laviña, Eduardo T. (Animo Repository, 1976)
v. 1. The proposed guidance program of the Philippine College of Commerce (PCC) Laboratory High School was set-up based on the needs of the students, teachers and the school, which were determined in the survey conducted in the school environment through the use of survey questionnaires for teachers and students, interviews, and utilization of school records. The responses of the teachers in the survey questionnaires were favorable and significant. The result of the chi-square in each item in the said questionnaires were all higher than the table value, which indicated that the responses were not based on chance or guess. Likewise, the students responded favorably to an organized guidance program. Based on the needs and problems gathered in the survey, the following guidance services were selected : Individual Inventory Service, Counseling Service, Testing Service and Information Service. The evaluation of the program will be conducted by a committee to be created upon the implementation of this proposed program whose members will be composed of some teachers and school administrators who will be selected on the merit of their achievement and research orientation. v. 2. This paper tests the validity and predictive ability of the five predictor variables used in this study, namely : National College Entrance Examination Overall Score, DLSU Admission Tests, specifically, Achievement Test, Reading Grade Placement Test, Mathematics-Cooperative Test and High School Grade Average, in predicting the academic performance in the first semesters of freshmen students in the Liberal Arts (LA) Degree Program of De La Salle University (DLSU). The 129 subjects of this study were chosen through random sampling. The information gathered from the computer were the means, standard deviations, simple correlation coefficient, multiple correlation coefficient, regression coefficients, and the standard error of estimate of multiple correlation. Other tools used were statistical tables, F-test, T-test, regression b equation, and multiple regression equation. The results of the study proved that all the abovementioned predictor variables were useful in determining who among the applicants should be admitted to the LA Degree Program of DLSU. Also, the variables were effective in predicting the academic performance of the applicants of freshmen students. The following conclusions were arrived at based on the results of the study : 1) A student with a good reading comprehension has greater chances of success to meet the academic requirements of DLSU in its LA Degree Program. 2) A student with a good academic grades in his high school has more chances to meet the academic requirements of the LA Degree Program of DLSU. 3) A student with a good reading comprehension and academic grades in high school is in a better position to achieve the academic requirements of DLSU in its LA Degree Program. Further, to facilitate admission decisions, the expectancy and prediction tables were constructed on the basis of results and findings obtained in this study.